The use of information technology in accounting - I.V. Zhyhlei; S.M. Laichuk; I.R. Polishchuk (Економіка, управління та адміністрування)
The study explores the formation of the information industry in Ukraine and identifies the application of information technology in organizing and conducting accounting by various economic entities. The authors established that digitalization of accounting indicates a transition from traditional accounting methods to the use of digital technologies and electronic systems. For the effective implementation and management of accounting digitalization processes, several key disciplines are recommended for preparing future accountants and the skills they will acquire while studying these disciplines. The main principles of organizing accounting using information technology are characterized, including the selection of appropriate accounting software, data security, integration with other systems, staff training, automation of accounting processes, compliance with current legislation, monitoring, and analytics, as well as technical support. The study highlights drawbacks that may arise when using accounting software, such as insufficient harmonization with international standards, the need for constant updates, high costs of accounting software, complex licensing and registration procedures for software products, lack of uniform standards for all industries, cybersecurity, and uncertainties in taxation. The conclusion is drawn that the unquestionable advantages of using digital technologies in accounting impact the increased qualifications required for accounting professionals and necessitate changes in the company’s management structure, recruitment of new personnel, and training of existing staff.